2023
DOI: 10.1093/nar/gkad007
|View full text |Cite
|
Sign up to set email alerts
|

The tRNA identity landscape for aminoacylation and beyond

Abstract: tRNAs are key partners in ribosome-dependent protein synthesis. This process is highly dependent on the fidelity of tRNA aminoacylation by aminoacyl-tRNA synthetases and relies primarily on sets of identities within tRNA molecules composed of determinants and antideterminants preventing mischarging by non-cognate synthetases. Such identity sets were discovered in the tRNAs of a few model organisms, and their properties were generalized as universal identity rules. Since then, the panel of identity elements gov… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
63
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 62 publications
(85 citation statements)
references
References 426 publications
0
63
0
Order By: Relevance
“…This modification enhances the stacking of s 2 U with U35 to stabilize the anticodon structure, facilitating codon-anticodon interactions. s 2 U is also recognized by multiple aminoacyl-tRNA synthetases for efficient amino acylation[12]. Although elimination of this sulfur modification causes severe growth phenotypes in most organisms[39, 49], unexpectedly, the deletion of mnmA in Mtb did not attenuate growth of the pathogen in vitro , suggesting that the Mtb requirement for s 2 U modification differs from other organisms.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This modification enhances the stacking of s 2 U with U35 to stabilize the anticodon structure, facilitating codon-anticodon interactions. s 2 U is also recognized by multiple aminoacyl-tRNA synthetases for efficient amino acylation[12]. Although elimination of this sulfur modification causes severe growth phenotypes in most organisms[39, 49], unexpectedly, the deletion of mnmA in Mtb did not attenuate growth of the pathogen in vitro , suggesting that the Mtb requirement for s 2 U modification differs from other organisms.…”
Section: Discussionmentioning
confidence: 99%
“…Chemical modifications of tRNA (tRNA modifications) are found in all kingdoms of life and fine-tune tRNA properties including mRNA decoding efficiency, recognition by aminoacyl-tRNA synthetases, half-life and structural stability [2,[10][11][12]. Modifications are prevalent in the anticodon loop, particularly at the first letter of the anticodon.…”
Section: Introductionmentioning
confidence: 99%
“…The realization that tRNA identity determinants -used by aminoacyl-tRNA synthetases to determine whether a tRNA is cognate -do not always include the anticodon, resulted in a major conceptual advance (15,16). It was found that many identity determinants are clustered in the tRNA acceptor stem (17), indeed in one case identity is determined by a single base pair in the acceptor stem (18)(19)(20). This led to the suggestion that a 'second genetic code' is written in the acceptor stem of tRNA and read by aa-tRNA synthetases (21).…”
Section: Introductionmentioning
confidence: 99%
“…Aminoacyl-tRNA synthetases recognize their cognate tRNAs through individual bases or structural motifs within the tRNA called identity elements [15][16][17]. For most tRNAs, the anticodon is the main identity element, providing a direct link between the genetic code and amino acid being incorporated.…”
Section: Introductionmentioning
confidence: 99%